PENERAPAN METODE BERCERITA DENGAN SOCIAL STORY UNTUK MENINGKATKAN KEMAMPUAN BERBICARA ANAK AUTIS DI SEKOLAH DASAR - Salam, Abdul (Jurnal Pendidikan Khusus, 2017)
Abstract : This research was formed background by the speaking disorder that was owned by children with autism. The speaking ability of children with autism have in asking questions, answering questions, and providing responses still need to be improved. The speaking ability of children with autism in this research was improved through the storytelling method with social story. The purpose of this research was to improve the speaking ability of children with autism through the application of storytelling method with social story. The research kind was experiment with Single Subject Research (SSR) arrangement of A-B design. The subject of his research was one child with autism in SD Negeri Percobaan Surabaya whose speaking ability was low. The results showed that the frequency range of speaking ability was done within 20 minutes at the baseline phase (A) 6-8 times and in the intervention phase (B) 12-20 times. The percentage of data overlap the baseline phase (A) to the intervention phase (B) was 0%. This suggested the intervention has an effect on target behavior that was speaking ability of children with autism. Based on these results can be concluded that the application of storytelling methods with social story can improve the speaking ability of children with autism in SD Negeri Percobaan Surabaya. Keywords: storytelling method, social story, speaking ability